(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
The combined effects of thermal and mechanical loadings on the distribution of stress-strain for E-glass fiber /polyester composite plates are investigated experimentally and numerically. The experimental work has been carried out by applying to a uniform temperature and tensile load on the composite plate inside the furnace and the deformation of plate measured by a dial gauge. Two parameter studies, the fiber volume fraction and fiber orientation on the stress-strain for plates subjected to identical mechanical and temperature gradient. The results presented showed that, the maximum absolute of total strain in longitudinal direction occurred at 50 N tension load and fiber angle 60º, while the minimum absolute values of it occurred at 15 N tension loads and fiber angle 0º. However the maximum absolute of total strain in transverse direction occurred at 15N tension load and fiber angle 0º, while the minimum absolute values of it are obtained at 50 N tension loads and fiber angle 60º. Also, the total strain in longitudinal and transverse direction decrease with increasing the fiber volume fraction. Comparison of the results in the experimental test with the numerical analysis of the total strain and evaluated the agreement between the two methods used, the maximum discrepancywas 20%.